Penerapan Akuntansi Belis dalam Adat Perkawinan Masyarakat Manggarai Nusa Tenggara Timur - Ambung, Marselina; Marce, Frederika Arciciliani; Jemaan, Marcelina D.; Lian, Yohanes Pemandi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research discusses the "belis" tradition in the Manggarai community of East Nusa Tenggara, which is a vital component of the traditional wedding process. "Belis" refers to the dowry given by the groom to the bride as a symbol of respect, family unification, and social responsibility. The aim of this research is to analyze the belis phenomenon from an accounting perspective, specifically focusing on the identification, measurement, and reporting of economic transactions related to this tradition.Using a qualitative approach, data was obtained through document studies from relevant journals. The findings reveal that the belis process involves several stages, including negotiations, the collection of funds, and the presentation of the dowry, which can take the form of money, livestock, and certain goods. During the transaction identification stage, donations and expenses are recorded, while the measurement of the purchase value is determined based on market prices, utilizing the concepts of historical cost and fair value in accounting.Financial reporting is conducted through manual recording, which serves to document transparency and accountability in the financial management of the belis tradition. This research illustrates that the belis tradition not only embodies cultural values but also possesses significant economic and social relevance, rendering it a pertinent subject for analysis from an accounting standpoint.